Incidental radiography findings of variations in root morphology: dens invaginatus or vertucci’s - Masyrifah, Nurul; Yunus, Barunawaty; Wulansari, Dwi Putri (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2026)
Objectives: The objective of this case report is to document the incidental finding in tooth 34 through panoramic radiography and discuss whether it falls into the category of dens invaginatus or Vertucci’s root canal morphology variations. Case Report: A 13-year-old male patient presented to RSGMP UNHAS with complaints of a decayed and painful lower left back tooth. Clinical examination revealed deep caries with perforation in tooth 35, and a periapical abscess was diagnosed. Panoramic and periapical radiographs were taken for diagnostic purposes. Radiographic analysis focused on identifying variations in the root morphology of adjacent teeth, specifically tooth 34. Conclusion: The incidental finding in tooth 34 through panoramic radiography emphasizes the importance of routine radiographic examinations in clinical practice. Early diagnosis and a clear understanding of this dental developmental anomaly are vital to ensuring the patient’s optimal oral health outcomes.